A resposta do consumidor ao uso do humor em serviços: os papéis de ameaça, credibilidade e familiaridade - Souza, Carla Moura de Melo (2011)
When people are happy they tend to evaluate products and services in a more positive manner. This seems to be the implicit objective behind the increasing use of humor in services: inducing a positive mood state. There are several examples of successful implementation of humor at hospitals, schools, training and educational facilities. Literature supports the practice of promoting consumer positive affective states: during evaluative judgments individuals use affective information in a congruent manner. However, sometimes humor cannot produce favorable attitudes and even magnifies negative ones. The goal of this thesis is to suggest and empirically test moderator variables that can explain this behavior. This thesis argues that when consumers anticipate potential damage to their well-being or self-esteem at the service, they feel threatened and evaluate service with humor poorly in comparison with the no humor alternative. The logic behind this hypothesis is that humor is ambiguous and his hostile and deprecating side would be considered in a situation of perceived threat, turning evaluations unfavorably or less favorably. The results show that threat moderates the relation between humor and service attitude and humor and willingness to try the service. This thesis also hypothesized that credibility and familiarity could reduce or eliminate the negative effect of threat on evaluations of services with humor. This hypothesis doesn’t hold for credibility, but it holds for familiarity. Therefore familiarity proved to be a safe ground to build service humor.